Clinical and Evidenced-Based Impact of Dietotherapy in Digestive Disorders - Salkhidinovna, Bekmuradova Makhsuda; kizi, Aliyeva Diyorakhon Ikromjon; kizi, Khamrayeva Shakhnoza Gayrat (American Journal of Biology and Natural Sciences, 2024)
Digestive disorders, such as irritable bowel syndrome (IBS), Crohn’s disease, and gastroesophageal reflux disease (GERD), represent a major global health challenge, affecting millions worldwide and severely impacting quality of life. This study investigates the efficacy of dietotherapy—therapeutic dietary interventions—in managing these conditions. Utilizing an observational design, the research included 100 participants divided into IBS, Crohn’s disease, and GERD groups, who followed condition-specific dietary regimens for 12 weeks. Key findings indicate significant symptom relief: a 40% reduction in IBS symptoms with the low-FODMAP diet, a 35% improvement in inflammatory markers for Crohn’s patients on the Mediterranean diet, and a 25% decrease in GERD symptom severity with a GERD- friendly diet. Compliance rates were high (84-87%), with minimal adverse effects. The study underscores the effectiveness of dietotherapy as a non-invasive treatment, highlighting its potential for integration into standard care practices. However, it also identifies critical gaps, including the need for long-term studies and research into dietotherapy’s applicability in diverse populations. Future research should focus on longitudinal outcomes and personalized dietary approaches to further enhance therapeutic efficacy and patient outcomes.